Organically modified silicas on metal nanowires - Dean, Stacey L (Langmuir : the ACS journal of surfaces and colloids, 2010)
Organically modified silica coatings were prepared on metal nanowires using a variety of silicon alkoxides with different functional groups (i.e., carboxyl groups, polyethylene oxide, cyano, dihydroimidazole, and hexyl linkers). Organically modified silicas were deposited onto the surface of 6-μm-long, ∼300-nm-wide, cylindrical metal nanowires in suspension by the hydrolysis and polycondensation of silicon alkoxides. Syntheses were performed at several ratios of tetraethoxysilane to an organically modified silicon alkoxide to incorporate desired functional groups into thin organosilica shells on the nanowires. These coatings were characterized using transmission electron microscopy, X-ray photoelectron spectroscopy, and infrared spectroscopy. All of the organically modified silicas prepared here were sufficiently porous to allow the removal of the metal nanowire cores by acid etching to form organically modified silica nanotubes. Additional functionality provided to the modified silicas as compared to unmodified silica prepared using only tetraethoxysilane precursors was demonstrated by chromate adsorption on imidazole-containing silicas and resistance to protein adsorption on polyethyleneoxide-containing silicas. Organically modified silica coatings on nanowires and other nano- and microparticles have potential application in fields such as biosensing or nanoscale therapeutics due to the enhanced properties of the silica coatings, for example, the prevention of biofouling